Evaluation of optimum fiber length of bamboo fiber reinforced concrete - Jeremy, Chong Zhineng (2018)
This research deals with the experimental study of the behavior of bamboo fiber with different fiber lengths and to study its effect as fiber reinforcing material. The species of bamboo that used throughout this experiment are the same species which is Gigantochloa scortechinii or commonly known as buluh semantan. The raw bamboo is delivered from the bamboo grove in Raub, Pahang which supplied by the local. The extractions of fiber are done based on the combined technique of chemical and mechanical using only 10% of w/v of sodium Hydroxide throughout the treatment process. In order to determine the bamboo physical and mechanical properties, a series of physical and mechanical test are done throughout this experiment and the composite samples are being mechanically tested in 3, 7, 14, and 28 days. The tests that has been conducted are bamboo water absorption test, compression and flexural tests. A total of 15 samples of concrete cubes and beams respectively are prepared including the control samples of 3 for each experiment groups for mechanical test. The cube sample and beam sample size used in this research are 100 mm x 100 mm x 100 mm and 100 mm x 100 mm x 500 mm respectively. Based on the results, it shows that the bamboo fiber in overall has only little contribution towards the improvement of concrete strength but significantly enhanced the concrete beam flexural strength which maximum up to 15%. The increase of fiber length leads to the increment of flexural strength but when it exceeds 38 mm, the performance decreased. Hence, it can be concluded that the optimum length for bamboo fiber reinforced concrete is 38mm.